Copper- and phosphine-free nickel(II)-catalyzed method for C-H bond alkynylation of benzothiazoles and related azoles - Patel, Ulhas N.; Punji, Benudhar (Asian Journal of Organic Chemistry, 2018)
A phosphine-free nickel(II)-catalyzed method for the C(2)-H bond alkynylation of (benzo)thiazoles, (benz)imidazoles, and oxazoles is described. Well-defined and air-stable (Phen)NiCl2 catalyst efficiently catalyzes the coupling of diverse azoles with alkynyl bromides without the use of a copper co-catalyst, and the method tolerates synthetically important functional groups. Preliminary mechanistic studies on this Ni-II-catalyzed alkynylation emphasize the homogeneous nature of the catalyst, and rule out a radical manifold for the reaction. The synthetic utility of this Ni-catalyzed method is demonstrated by further functionalizing the alkynylated benzothiazoles to 3-methyl-2-(alkynyl)benzo[d]thiazolium salts that are known DNA cleaving agents.
Keywords: alkynylation; azoles; C-H activation; heterocycles; Nickel